Optimalisasi produk cicilan dan tabungan emas di BSI KCP Kediri bandar sebagai strategi penguatan investasi syariah - Hariyono, Bunga Prameswari (Maliki Interdisciplinary Journal, 2025)
This study examines the optimization of gold savings and gold installment products at Bank Syariah Indonesia (BSI) KCP Kediri Bandar as a strategy to strengthen Islamic investment. The background of this research lies in the growing public interest in halal investments that comply with Sharia principles, with gold serving as a preferred instrument due to its value stability and resilience against inflation. The gold savings product is designed for customers who wish to invest gradually through the conversion of deposits into gold units, while the gold installment product applies the murabahah contract, enabling immediate gold ownership with flexible installment payments. Marketing strategies are carried out through education, active promotion, and digitalization of services while upholding Sharia compliance. The findings indicate that these two products not only reinforce BSI’s role as the government-appointed gold bank but also support the enhancement of Sharia financial literacy and inclusion in society. The optimization and synergy between gold savings and gold installment products have proven effective in reaching diverse customer segments and in strengthening public trust in Sharia-based investments.